O direito achado nos Pampas: o que os conflitos socioambientais atuais em torno da mineração no bioma brasileiro têm a dizer sob a ótica da sociobiodiversidade - Curvello, Isabel Foletto (2023)
The Pampa Biome is considered rich in biological diversity and cultural diversity, characterized as a territory where a series of communities have their roots and develop their cultures. This work focuses on a region of the biome where two mining projects are in vogue, in the Alto Camaquã region, to investigate existing non-local socioenvironmental conflicts, as well as the sense of sociobiodiversity that manifests itself in resistance to mining projects, such as the objective of answering the question that constitutes the research problem: what are the limits and possibilities for mining the Pampa in an updated state? Then, based on a systematic-complex approach methodology, and also carrying out semi-structured interviews and participant observation combined with organized resistance to projects, the work explores three concepts: socio-biodiversity and the reason why Pampa can be considered socio-biodiverse; neoextractivism and socio-environmental conflicts, referring mining to the main expression of neoextractivism discussed here and, finally, to the emergence of a new understanding about the production of rights, based on Law Found on the Street and Mining-Free Territories. In this context, it is possible to understand that there is strong resistance to neo-extractivist projects in Pampa, which is a consequence to the connection that exists between the countryside and Pampa and also to the connection between the population and the river, essential to the development of agropastoral activities carried out in the region. So, the conclusion of the work is that Alto Camaquã still carries distinctive characteristics of a biome that we see losing a large part of its sociobiodiversity due to the advancement of neo-extractive activities. Therefore, it is proposed that the local area be considered mining-free territory, a concept that arises in community discussions, but which can begin to guide public mining policies in the country, as we saw happen in the production of some laws, making up what It’s called Law Found in the Pampas.